A qualitative study of persons who inject drugs but who have never helped others with first injections: how their views on helping contrast with the views of persons who have helped with first injections, and implications for interventions - David M. Barnes; Don C. Des Jarlais; Margaret Wolff; Jonathan Feelemyer; Susan Tross (BMC, 2018)
Abstract Background Transitioning from non-injection to injection drug use dramatically escalates health risks. Evidence suggests that people who inject drugs (PWID) help in a majority of others' first injections, yet these helpers represent only a minority of experienced PWID. Recent research has provided insight into this helping process, as reported by helpers. PWID who have never helped, although the majority of PWID, have not previously been the focus of study. To address this gap, we give primary voice to non-helpers' perspectives on the helping process, while also comparing their views with persons in our sample who have helped with first injections. Finally, we consider how non-helpers' perspectives can inform harm reduction interventions to reduce, or make safer, initiation into injecting drug use. Methods We conducted audio-recorded, qualitative interviews with 23 current opioid injectors on Staten Island, NY, where the opioid epidemic is pronounced. Seventeen had never helped with first injections and 6 had. Interviews were transcribed verbatim, and three coders used a consensus-developed codebook to code all interviews. Framework analysis was used to identify overarching themes. Results We identified three key themes in non-helpers' discourse around not helping: altruistic motivations to prevent immediate and delayed harms to individuals injecting for the first time; inhibition due to negative assessments of their own injecting skills; and absolutist ethical convictions against helping. Non-helpers differed from helpers on each theme. Conclusions Because most PWID have never helped with first injections, their perspectives on helping warrant consideration and can inform harm reduction interventions to reduce, or make safer, transitions to injection drug use. Their perspectives can be used to broaden the factors PWID consider around questions of promoting injection and helping with others' first injections, including considerations of the moral issues involved in choosing to help or not to help.